Do Teachers Require Specific Skills to Implement Education for Sustainable Development (ESD)? Theoretical Framework, Study Design, and First Results - Hellberg-Rode, Gesine; Schrüfer, Gabriele; Hemmer, Michael (Journal of Geography Education, 2014)
Since the UN conference of 1992 in Rio de Janeiro, it has been explicitly called for Education for Sustainable Development (ESD) as a sociopolitical instrument to create a sustainable development. More than twenty years later and at the end of the UN decade "Education for Sustainable Development" this demand has neither reached the awareness of German teachers yet, nor has it been implemented accordingly in general education schools. Presumably one reason for this is that teachers’ professional competences do often not include ESD-specific skills. Up to now, there has been no scientific proof if or which professional competences regarding ESD are actually required to design lessons that facilitate learners’ ESD relevant competences. To answer this question we conducted a two-stage Delphi-study with twelve experts in 2012. The study focused mainly on professional knowledge consisting of content knowledge, pedagogical content knowledge and pedagogical knowledge.